Influence of Ammonia Contamination on HT-PEM Fuel Cell Platinum Catalyst. (8th September 2020) - Dushina, Anastasia; Schonvogel, Dana; Fischer, Yannis; Büsselmann, Julian; Dyck, Alexander; Wagner, Peter
Abstract : In this work the effect of NH3 contamination on platinum catalyst has been investigated in the frame of a high temperature polymer electrolyte membrane single fuel cell as well as rotating ring disk electrode measurements (RRDE) using phosphoric acid electrolyte. In the first part single cell operation in presence of 10 ppm NH3 in the cathode gas combined with electrochemical impedance spectroscopy was performed with a fuel cell test bench. In the second part of work RRDE experiments were accomplished in the presence of 10 and 100 ppm of NH4 H2 PO4 contamination in 0.5 mol L -1 H3 PO4 . It was revealed that platinum catalyst is strongly affected by ammonia contamination while the increasing ammonium concentrations reduce the electrochemical surface area (ECSA) of the Pt catalyst. These observed losses of ECSA were associated to adsorbed nitrogen compounds on the catalyst surface.